Reconstruction of Soft-Tissue Defects at the Foot and Ankle after Oncological Resection - Ring, Andrej; Kirchhoff, Pascal; Goertz, Ole; Behr, Bjorn; Daigeler, Adrien; Lehnhardt, Marcus; Harati, Kamran (Frontiers in Surgery, 2016)
Introduction: Solid malignancies at the foot and ankle region are rare and include mainly soft tissue sarcomas, bone sarcomas and skin malignancies. Complete surgical resection with clear margins still remains the mainstay of therapy in these malignancies. However, attainment of negative surgical margins in patients with locally advanced tumors of the foot and ankle region may require extensive surgery and could result in loss of extremity function. In these circumstances, plastic surgical techniques can frequently reduce functional impairment and cover soft tissue defects, particularly in cases of large tumor size or localization adjacent to critical anatomic structures, thereby improving the quality of life for these patients. The aim of this article is to illustrate the various treatment options of plastic surgery in the multimodal therapy of patients with malignant tumors of the foot and ankle region. Material und methods: This article is based on the review of the current literature and the evaluation of the author’s own patient database. Results: The local treatment of malignant extremity tumors has undergone major changes over the last few decades. Primary amputations have been increasingly replaced by limb-sparing techniques, preserving extremity function as much as possible. Although defect coverage at the foot and ankle region is demanding due to complex anatomical features and functional requirements, several plastic surgical treatment options can be implemented in the curative treatment of patients with malignant solid tumors in this area. Soft tissue defects after tumor resection can be covered by a variety of local flaps. If local flaps are not applicable, free flap transfers, such as the anterolateral thigh (ALT) flap, parascapular flap or latissimus dorsi flap, can be utilized to cover nearly all kinds of defects in the foot and ankle region. Conclusion: Soft tissue reconstruction in the foot and ankle region is a vital component of limb-sparing surgery. It enables complete resection of locally advanced tumors and subsequent adjuvant radiotherapy. Modern plastic surgical techniques should, therefore, be integrated in the multimodal treatment concept of malignancies in the foot and ankle region.